Response of submerged macrophytes of different growth forms to multiple sediment remediation measures for hardened sediment - Chao, Chuanxin; Chen, Xiaorong; Wang, Jie; Xie, Yonghong (Frontiers in Plant Science, 2024)
Climate change and intensified human activities have disrupted the natural hydrological regime and rhythm of river-connected lakes, extending the dry season, increasing water loss, and exposing previously submerged lake floors. This exposure has led to significant sediment hardening, which directly impacts submerged macrophytes. However, strategies to mitigate the negative effects of hardened sediments and promote the growth and development of submerged macrophytes remain largely unexplored. In this study, we selected typical hardened sediment from Dongting Lake to investigate the response of different growth forms of submerged macrophytes to multiple sediment remediation measures (loosening and litter addition) using a mesocosm experiment. The results indicated that loosening alone uniformly benefited all submerged macrophytes by increasing total biomass, relative growth rate (RGR), and the root/shoot ratio. Additionally, loosening altered the root traits of submerged macrophytes, promoting maximum root length (MRL) while reducing average root diameter (ARD). Moreover, different submerged macrophytes exhibited species-specific responses to the combination of loosening and litter addition. Notably, the combination of loosening and adding Miscanthus lutarioriparius litter had an antagonistic effect on the growth of Potamogeton wrightii and Myriophyllum spicatum. The response of functional traits of submerged macrophytes with similar growth forms to the same treatment was consistent. Our findings suggest that future sediment remediation efforts should consider matching specific treatments with the growth forms of submerged macrophytes to achieve optimal outcomes.